A System Dynamics Approach to Catalyze Environmental Sustainability in Higher Education and Research Organizations - Miralles-Wilhelm, Fernando (Digital Repository of Theses, 2026)
Environmental sustainability has become a strategic imperative for higher education and research organizations (HEROs), yet many HEROs struggle to translate sustainability commitments into durable, system-wide outcomes. Existing research has largely relied on static frameworks, descriptive case studies, and performance rankings, offering limited insight into the dynamic processes through which sustainability strategies evolve, stabilize, or erode over time. This dissertation addresses this gap by examining sustainability transformation in higher education through the lenses of organizational change, strategic management, dynamic capabilities, and innovation and entrepreneurship. The dissertation develops and applies a System Dynamics (SD) modeling framework to capture the feedback mechanisms, delays, and path dependencies that shape sustainability performance in complex academic organizations. Five policy scenarios are simulated: governance and strategy integration, dynamic capability building, organizational change and cultural transformation, sustainability innovation ecosystem acceleration, and institutional context differences between U.S. and international higher education systems. Model calibration and validation draw on publicly available AASHE STARS data, enabling empirical grounding while preserving theoretical rigor. Results demonstrate that no single policy lever is sufficient to generate sustained sustainability performance. Instead, durable progress emerges from coordinated and sequenced interventions that align governance structures, organizational capabilities, cultural dynamics, and innovation ecosystems. The findings highlight complementarities and trade-offs among policy approaches and reveal how institutional context conditions the pace and stability of sustainability transitions. A case study application to the University System of Maryland illustrates how the SD model can function as a strategic learning and decision-support tool for system-level leadership. The dissertation contributes to theory by integrating dynamic capabilities and sustainability transitions within a formal dynamic framework, and to practice by offering actionable insights for university leaders and policymakers seeking to manage sustainability as a long-term organizational transformation.